1981
DOI: 10.1002/cber.19811140531
|View full text |Cite
|
Sign up to set email alerts
|

Einführung von Sauerstoff‐Funktionen in die α‐Stellung von β‐Diketonen, 41) Direkte Acyloxylierung von 1,3‐Cyclohexandionen mit Diacylperoxiden

Abstract: Die direkte Acyloxylierung der 1,3‐Cyclohexandione 1 führt nur in Ausnahmefällen zu den Monoacyloxylierungsprodukten 4. Ihre Natriumsalze 5 dagegen liefern die unmittelbaren Folgeprodukte 8 einer Bisacyloxylierung. Diese sind jedoch in Gegenwart von Base instabil und erfahren unter Abspaltung molarer Menge Carbonsäure eine Umacylierung zu den Cyclohexadienonen 9. Der Mechanismus dieser Umacylierung wird aufgeklärt. Ausgehend von den Folgeprodukten einer Benzyloxycarbonyloxylierung wird eine bequeme Reduktonsyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1981
1981
2003
2003

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Diesters (115) of hydrates in the 5,5-disubstituted or spiro cyclohexanetrione series have been obtained by Schank et al 107 in low yields by reaction of the sodium salts of 1,3-diones with diacyl peroxides; monoesters were obtained from the neutral diones. Reaction of 115 with the corresponding sodium acylates resulted in conversion to monoesters 116 of the enolic form of the trione.…”
Section: Hydration (Scheme 37)mentioning
confidence: 99%
See 1 more Smart Citation
“…Diesters (115) of hydrates in the 5,5-disubstituted or spiro cyclohexanetrione series have been obtained by Schank et al 107 in low yields by reaction of the sodium salts of 1,3-diones with diacyl peroxides; monoesters were obtained from the neutral diones. Reaction of 115 with the corresponding sodium acylates resulted in conversion to monoesters 116 of the enolic form of the trione.…”
Section: Hydration (Scheme 37)mentioning
confidence: 99%
“…The two recent examples of trione reduction, discussed below, involved cyclic compounds. Schank et al 107 reduced bis-dibenzyl ethers (183) of 5,5-dimethyl and 5,5-spirocyclohexanetrione hydrates (from reaction of bisbenzyloxycarbonyl peroxide with the sodio derivative of dimedone) catalytically over Pd/C in methanol-ethyl acetate to obtain the dihydrotriones 184 (reductones). Schank and Blattner 21 showed that the gem-chloroformates 181 (R ) H) were reduced by sodium iodide to formate esters of 184; hydrolysis gave 184.…”
Section: F Reductions (Scheme 52)mentioning
confidence: 99%